Design And Characterization Of All Fiber Optical Filters - Veeriah, Sutharsanan (2006)
An all fiber device is important in an optical fiber communication system as it exhibits low splicing loss, small in size, and has ease of packaging. In this dissertation, designs and analysis of tunable all-fiber devices for optical fiber communications are investigated.